Students' Perception of Padlet in Facilitating Collaborative Learning in the Morphology Classroom - Rahmawati, Tira; Dewi, Sinta; Sofyawati, Eva Devi; Hamzah, Amir (Fakultas Ilmu Budaya, Universitas Brawijaya, 2026)
The present study examines the students’ perceptions of the use of Padlet to support the collaborative learning during English Morphology course. The study was carried out through survey approach through which the data were collected through a 5 point-Likert scale questionnaire administered to 50 seventh-semester students of the English Education Study Program at one of the private universities in Indonesia. To complement the survey data, the interviews were done to the 9 selected participants. The data analysis focused on the students’ perception towards Padlet, its benefits and challenges that present. The results showed that the students have general positive perceptions toward Padlet, especially in terms of its ease of use, its impacts on students ‘engagement and learning motivation. Padlet was considered helpful in facilitating the students to understand abstract morphological concepts, support their analytical skills, and facilitate feedback and discussion. Regardless of the benefits, several barriers such as technical issues, potential distraction and lack of teacher’s role remain a challenge. The findings indicate that Padlet has the potential to support the process of linguistic learning if it is supported by adequate infrastructure, appropriate teaching strategies and the active roles of teachers. Further studies are recommended to examine the effectiveness of Padlet compared to other platforms, integrate it with the innovative learning model and assess its impact on the students’ academic performance and their 21st century skills.